Human brain plastination - Mohammed, Raed Hamzah; Abdel Wahab, Emad Mohamad Nafie (IIUM Press, International Islamic University Malaysia, 2017)
Sheet plastination is a technique for tissue slices preservation that gives real anatomical specimens and its slices considered as a good reference in cross section anatomy as well as in radiology. This research aims to compare the shrinkage area between plastinated human brain slices using two different dehydration methods on a single human cadaver brain. This study included using of nineteen slices of one human brain. The brain was fixed in 10% formalin for three months, washed and cut in two halves in the sagittal plane. Both brain halves were sliced at a thickness of 3mm. From the left half 9 slices were selected for the standard method of dehydration (20°C for one week for full process the concentration of acetone was 95% and 100% in two steps) and 9 slices from the right half for the revised method (-25°C for two weeks for full process the concentration of acetone was 80%, 85%, 90%, 95% and 100% in five steps). To measure the surface area for each slice, it was put on a A4 sized white plastic board measuring 210 × 297 millimeters and a picture was taken before dehydration (before plastination) and after curing process (after plastination) by using a normal digital camera 13.0 megapixel (MP). The left and right brain slices were then immersed at 20°C for one day in P40 resin only, and then impregnated at room temperature (20°C) for 24 hours under vacuum (50mmHg) condition. All impregnated slices were cured with a hardener (1.5ml /100ml). The picture of the brain slices were uploaded into a computer and analysed by using Photoshop 10 CS3 software. The surface area of the brain slices was calculated before dehydration and after curing. The processed slices in standard dehydration method showed a shrinkage rate of 15.14%, in comparison to the slices that were dehydrated by revised method that showed a shrinkage rate of 9.42%. The statistical analyses were carried out by Microsoft Excel t-Test. These results were considered significant at p < 0.05 level. In conclusion, the revised dehydration method gives less shrinkage rate than standard method in brain sheet plastination.